2022
DOI: 10.1155/2022/4471455
|View full text |Cite|
|
Sign up to set email alerts
|

Visual Identification of Mobile App GUI Elements for Automated Robotic Testing

Abstract: Automated robotic testing is an emerging testing approach for mobile apps that can afford complete black-box testing. Compared with other automated testing approaches, automatic robotic testing can reduce the dependence on the internal information of apps. However, capturing GUI element information accurately and effectively from a black-box perspective is a critical issue in robotic testing. This study introduces object detection technology to achieve the visual identification of mobile app GUI elements. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Recent research (Yap et al ., 2021) has suggested that robotics and automation can reduce construction accidents. These technologies improve hazard detection, safety planning and inspections and increase safety awareness (Xue et al ., 2022; Yap et al ., 2021; Hou et al ., 2020). Wearable technologies can also monitor workers' health and detect early signs of overwork or stress (Xue et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research (Yap et al ., 2021) has suggested that robotics and automation can reduce construction accidents. These technologies improve hazard detection, safety planning and inspections and increase safety awareness (Xue et al ., 2022; Yap et al ., 2021; Hou et al ., 2020). Wearable technologies can also monitor workers' health and detect early signs of overwork or stress (Xue et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These technologies improve hazard detection, safety planning and inspections and increase safety awareness (Xue et al ., 2022; Yap et al ., 2021; Hou et al ., 2020). Wearable technologies can also monitor workers' health and detect early signs of overwork or stress (Xue et al ., 2022). However, construction adoption faces challenges, especially cost issues, especially for small- and medium-sized businesses, mainly in developing countries (Salento, 2017; Karakhan et al ., 2018; Xue et al ., 2022; Wu et al ., 2021, 2023; Chauhan, 2021; Okpala et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%